The teacher training institute: issue of qualification / Azmimie Shazwanie Abd Haris and Siti Zulaika Bandar - Abd Haris, Azmimie Shazwanie; Bandar, Siti Zulaika (2016)
The purpose of this study is to investigate the qualification required to enroll in teacher training college and to find out the consistency qualification requirement of the teacher training college in Malaysia. The issues are when a teacher training college has stopped recruiting KPLI. The research was conducted in two (2) in Institut Pendidikan Guru Kampus Kota Bahru, Kelantan and Institut Pendidkan Guru Kampus Tawau, Sabah. The sample population was 234 respondents using the questionnaire. Descriptive statistics were used in the analysis of data. Crosstabulation analysis used to show the answer given by the respondents. The data using the statistical procedure of a social system (SPSS) which can bring meaningful and can be interpreted. The data were collected from primary and secondary data. Whereas it was useful in term of understanding and the accuracy of the information gained. From the researcher finding found that there were no consentency in qualification required to enroll in teacher training college in Malaysia.